Piccardi-Lassueur-Graham-Little syndrome associated with frontal fibrosing alopecia - Andrea Alejandra Catalán Griffiths; Maribel Iglesias Sancho; Ana Iglesias Plaza (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Piccardi-Lassueur-Graham-Little syndrome is a rare entity characterized by progressive scarring alopecia of the scalp and keratotic papules on hairless skin, associated with non-scarring alopecia in the axilla and pubic area or lichen planus lesions. We describe the case of a 70-year-old woman who presented a Piccardi-Lasseur-Graham-Little syndrome, along with frontal fibrosing alopecia.